MODERN TRENDS OF EUROPEAN UNION’S MIGRATION POLICY - Anna Sergeevna Matveevskaya (Science and Innovation Center Publishing House, 2016)
Background research consists in exacerbating migration crisis in Europe, accompanied by many thousands of illegal border crossings of the EU, the death of migrants suffering a disaster in the Mediterranean Sea while trying to reach European coast, as well as changes in the asylum system. The subject of research is the migration policy of the European Union, reacting to new threats and challenges of the migration crisis. The aim of the article is to examine the decisions taken by the EU institutions and documents, as well as analysis of joint international activities of EU Member States in solving the current migration problems. Method of research is a theoretical analysis of the effect of migration on the economic and social life of the EU; comparative method for estimating the effectiveness of the European countries documents aimed to resolve migration problems. The results showed that the EU’s migration policy has achieved some significant results, such as the solution of the problem on rescue of migrants in distress in the Mediterranean Sea, or the security of the external borders of the EU. But in general, it should be noted, low efficiency and productivity of EU migration policy, which is associated with a number of economic, political and geopolitical factors. Field of application results. The results can serve as a basis for further development and improvement of the immigration policy of the EU.